Bates' guide to physical examination and history taking. - Bickley, Lynn S. 4 0 16; 1928- Szilagyi, Peter G.;Bates, Barbara; 5 (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
A fully illustrated textbook for students learning to examine and diagnose patients, from an evidence-based perspective, that covers examination techniques, common medical equipment, vital signs, symptoms, pain scales, special patient populations, and other related topics, with extensive citations from the clinical literature. Includes a CD-ROM.
Includes bibliographical references and index.
Adult;Adult.
System requirements not stated.
Keywords: 2 -- 0; 6; methods.;methods. -- Physical diagnosis.;Medical history taking.;Physical Examination;Medical History Taking;Diagnosis.;CD-ROMs.; 20; CD-ROMs.